Discrete-time mixed-integer programming models for short-term scheduling in multipurpose environments - Lee, Hojae; Maravelias, Christos T. (Computers & chemical engineering, 2017)
•We propose novel MIP models for scheduling in multipurpose facilities.•Common discrete-time grid enables handling of shared utilities.•Models are extended to account for process features not previously addressed.•Applicability and performance of models are shown through case studies. We present new discrete-time mixed-integer linear programming formulations for short-term scheduling in multi-purpose batch plants, the most general sequential production environment. We first discuss how multi-purpose batch plants can be expressed using State-Task Network and Resource-Task Network representations through batch-based definition of states (resources) and tasks. We then develop two models based on each representation that account for limited intermediate storage, and discuss extensions such as limited shared resources and time-varying resource availability/cost. Finally, we present several case studies to illustrate the applicability and performance of the proposed models.